Interpretasi Sintaksis Dan Gaya Bahasa Dalam Syair Al-I’tiraf Abu Nawas Terjemahan Arab-Indonesia: Kajian Tarkib Athfi Dan Tarkib Isnadi - Angela Balkist, Vhebe; Sari Lubis, Rizka Novita; Nurrahma, Laila; Dzikratunnisa Pangestu, Naila; Sakinah, Nayla; Zulfan Tsauri, Muhammad Azriel; Edidarmo, Toto (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This research aims to analyze the syntactic structures and stylistic features found in the Al-I'tir?f poem by Abu Nuwas, both in its original Arabic version and its Indonesian translation. The study focuses on two key syntactic structures, namely tark?b ‘athfi (coordinative structure) and tark?b isn?di (predicative structure), exploring how these structures convey spiritual and aesthetic meanings. By employing a contrastive analysis, the research also examines how these syntactic structures transform in the Indonesian translation, preserving or shifting their meaning and stylistic impact. The findings reveal that these syntactic structures play a significant role in the expression of religious humility and repentance, as well as the emotional intensity of the poem. The study contributes to the understanding of classical Arabic syntax, its stylistic implications, and the challenges of translating such texts into Indonesian.